Sosialisasi Penggunaan Peanut Ball untuk Mengurangi Nyeri Persalinan Kala 1 di Desa Moncongloe Bulu Kabupaten Maros - Nurjannah Supardi (Pusat Riset dan Inovasi Nasional, 2022)
In order to improve the community development business system to be more productive and efficient, technology is needed. The introduction of technology that has developed in society is technology that has been developed in a modern way, or what is known as